2022
DOI: 10.3389/fneur.2022.757523
|View full text |Cite
|
Sign up to set email alerts
|

Post-surgery Rehabilitative Intervention Based on Imitation Therapy and Mouth-Hand Motor Synergies Provides Better Outcomes in Smile Production in Children and Adults With Long Term Facial Paralysis

Abstract: Rehabilitation after free gracilis muscle transfer (smile surgery, SS) is crucial for a functional recovery of the smiling skill, mitigating social and psychological problems resulting from facial paralysis. We compared two post-SS rehabilitation treatments: the traditional based on teeth clenching exercises and the FIT-SAT (facial imitation and synergistic activity treatment). FIT-SAT, based on observation/imitation therapy and on hand-mouth motor synergies would facilitate neuronal activity in the facial mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(92 reference statements)
1
1
0
Order By: Relevance
“…A previous study confirmed the improvement of BH and PF using Emotrics, displaying improved eye function after plastic surgery on the eyelids that did not close in facial palsy [9]. Previous studies have also shown improvements in SA, CE, and DS using this program, representing oral functions, as well as additional progress in other indicators after rehabilitation treatment or plastic surgery that enabled spontaneous smiling [12][13][14]. Based on these studies, Emotrics parameters are well-reflected by clinical improvements.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A previous study confirmed the improvement of BH and PF using Emotrics, displaying improved eye function after plastic surgery on the eyelids that did not close in facial palsy [9]. Previous studies have also shown improvements in SA, CE, and DS using this program, representing oral functions, as well as additional progress in other indicators after rehabilitation treatment or plastic surgery that enabled spontaneous smiling [12][13][14]. Based on these studies, Emotrics parameters are well-reflected by clinical improvements.…”
Section: Discussionsupporting
confidence: 63%
“…Emotrics possesses a significant advantage in automatically evaluating the differences in landmark positions between two images. It has been utilized in assessing the effectiveness of various plastic surgeries and rehabilitation treatments [9,[12][13][14]. However, since it was not originally designed for the purpose of the facial palsy severity scale, there is insufficient evidence to support the reliability and validity of its automatic evaluation, particularly when compared to manual evaluation methods or the HB grades.…”
Section: Introductionmentioning
confidence: 99%